Low lymphocyte-to-monocyte ratio, calcitriol level, and CD206 level predict the development of acute-on-chronic liver failure in patients cirrhosis with acute decompensation. Issue 3 (23rd January 2023) - Kuo, Nai-Rong; Hou, Ming-Chih; Chu, Wei-Chi; Yang, Ying-Ying; Huang, Chia-Chang; Li, Tzu-Hao; Lee, Tzung-Yan; Liu, Chih-Wei; Liao, Tsai-Ling; Hsieh, Shie-Liang; Lin, Han-Chieh
Abstract : Background: Cirrhosis-related acute-on-chronic liver failure (ACLF) is associated with high morbidity and mortality rates. Prognostic models of ACLF have been developed; however, few studies have focused on the occurrence of ACLF. This study aimed to identify the factors that predict the development of ACLF, hepatic encephalopathy (HE), and infection in patients with cirrhosis. Methods: Patients with cirrhosis were enrolled, and the serum levels of calcitriol, Cluster of Differentiation 26 (CD206), and macrophage-inducible lectin receptor (Mincle) were measured, and lymphocyte-to-monocyte ratio (LMR) and neutrophil-to-lymphocyte ratio were calculated; all the patients were tracked for 6 months. A generalized estimating equation (GEE) was used to assess the factors associated with ACLF development, HE, and infection. The aforementioned model was derived based on immunological markers, and receiver operating characteristic analysis with area under the curve (AUC) was adopted to evaluate accuracy. Results: After screening 325 patients with cirrhosis, 65 patients were eligible. In the GEE model, low levels of calcitriol (odds ratio [OR] = 3.259; 95% confidence interval [CI] = 1.118–8.929) and CD206 (OR = 2.666; 95% CI = 1.082–6.567) were associated with the development of ACLF, and the LMR was a protective factor (OR = 0.356; 95% CI = 0.147–0.861). Low calcitriol levels were a risk factor for HE (OR = 3.827) and infection (OR = 2.489). LMR was found to be a protective factor against HE (OR = 0.388). An immunological model for the discrimination of ACLF development within 6 months was proposed, with an AUC of 0.734 (95% CI = 0.598–0.869). Conclusion: Single and combined immunological markers, including low LMR and low levels of calcitriol and CD206, were promising for early prediction of the development of ACLF, HE, and infection in patients with cirrhosis.